The dynamic material properties of stabilised rammed earth materials using cement and calcium carbonate residue - Liu, Kewei; Walske, Megan; Zhou, Mi; Zhang, Xihong (SAGE, 2022)
The use of rammed earth (RE) as a construction material has recently received renewed interest due to its sustainability characteristics and potential for low-cost construction. Modern RE includes the addition of a binder to increase its performance. The mechanical performance of stabilised RE particularly the dynamic material properties is still not well understood. During the design life, a structure could experience dynamic loading. It is necessary to properly understand the dynamic properties of stabilised RE for safe applications. In this study, the quasi-static and dynamic material properties of cement and calcium carbonate residue (CCR) stabilised RE are experimentally investigated. The failure of the stabilised RE under different loading rates is investigated. Dynamic increase effect on cement and CCR stabilised RE are studied. The unconfined uniaxial compressive strength (UCS), Young’s modulus of the two types of stabilised RE at different strain rates are quantified. Empirical formulae of dynamic increase factor are derived for engineering application.